Genome‐wide association study identifies variation of glucosidase being linked to natural variation of the maximal quantum yield of photosystem II. Issue 1 (27th March 2019) - Hamdani, Saber; Wang, Hongru; Zheng, Guangyong; Perveen, Shahnaz; Qu, Mingnan; Khan, Naveed; Khan, Waqasuddin; Jiang, Jianjun; Li, Ming; Liu, Xinyu; Zhu, Xiaocen; Govindjee,; et al.
Abstract : The maximum quantum yield of photosystem II (as reflected by variable to maximum chlorophyll a fluorescence, F v / F m ) is regarded as one of the most important photosynthetic parameters. The genetic basis underlying natural variation in F v / F m, which shows low level of variations in plants under non‐stress conditions, is not easy to be exploited using the conventional gene cloning approaches. Thus, in order to answer this question, we have followed another strategy: we used genome‐wide association study (GWAS) and transgenic analysis in a rice mini‐core collection. We report here that four single‐nucleotide polymorphisms, located in the promoter region of β‐glucosidase 5 ( BGlu‐5 ), are associated with observed variation in F v / F m . Indeed, our transgenic analysis showed a good correlation between BGlu‐5 and F v / F m . Thus, our work demonstrates the feasibility of using GWAS to study natural variation in F v / F m, suggesting that cis ‐element polymorphism, affecting the BGlu‐5 expression level, may, indirectly, contribute to F v / F m variation in rice through the gibberellin signaling pathway. Further research is needed to understand the mechanism of our novel observation.